Pirólise solar catalítica com o uso de lentes de Fresnel - Martins, Marcus Paulo Barbosa (2020)
The increase in fossil fuel consumption has contributed to an energy shortage and the acceleration of global warming, leading to a search for renewable sources of energy such as solar, wind, and biomass. Microalgae are widely studied biomass sources for fuel generation via thermochemical processes, due to their great diversity of species, good environmental adaptability, short growth cycle, and because they are cultivated in environments that do not compete for agricultural land. The process of solar pyrolysis is a promising technology as it unites the use of biomass and solar energy in order to generate transportable and storable fuels, as well as chemicals of interest. The product of the greatest interest of rapid pyrolysis of microalgae is bio-oil, a liquid and viscous mixture composed of hundreds of chemicals. Among these compounds are many oxygenated and nitrogenous ones that give them undesirable properties. Several technologies aimed at improving bio-oil through deoxygenation and denitrogenation are being investigated, including the use of catalysts. Therefore, this study aimed to evaluate the potential of microalgae Spirulina platensis for the generation of fuels and chemicals of interest, via solar pyrolysis. Additionally, the performance of mixed oxides derived from hydrocalumite as catalytic precursors of the process was evaluated, aiming at improving the quality of the products generated. In this study, the analytical pyrolysis of the microalgae, in the absence of catalyst, indicated a reduction in the number of oxygenated compounds with the increase in temperature. A Central Composite Design associated with a Response Surfaces technique was used to evaluate the influence of reaction time and catalyst percentage on product yield and bio-oil quality obtained from solar pyrolysis. The maximum liquid yield achieved after an optimization study was 43.39%. Regarding the quality of the bio-oil, mixed oxides demonstrated good performance, since they decreased the amount of oxygenated and increased the relative percentages of hydrocarbons, as in the previous tests of catalytic micropyrolysis. The catalyst percentage of 29.29% was the most appropriate to maximize hydrocarbon yield, ensuring a relative amount of 55.14% of this product in the composition of bio-oil. Thus, the development of this work shows that under appropriate process conditions, solar pyrolysis is promising for obtaining fuels of interest.